Service quality evaluation of county-level public hospitals in Chongqing under smart healthcare - Yuantang Qiu; Chun Xiao; Jing Li (BMC, 2024)
Abstract Background This study explores patients' perceptions and expectations of smart healthcare services from the perspective of patient experience.The aim is to provide insights for the development of smart healthcare services in hospitals. Methods A cluster sampling method was used to select 10 public county-level hospitals from October to November 2021 in a municipality in southwestern China. Patient expectations and perceptions about smart healthcare services were assessed using SERVQUAL scale, which included 24 items across four dimensions: ability, application, platform, and effectiveness. The perception-expectation gap was calculated, and factors influencing this gap were analyzed. The Importance-Performance Analysis (IPA) model was then applied to evaluate the results. Results A total of 915 patients from outpatient and inpatient departments participated in the study. The average perception score was 3.86, while the average expectation score was 4.44, resulting in a gap of -0.58. Paired sample t-tests revealed significant differences between patients' perceptions and expectations across the 24 items (P < 0.05). IPA quadrant analysis identified 5 items in quadrant IV. A generalized linear model indicated that patients with a college degree, income between 2001 ~ 3500RMB, and income between 3501 ~ 5000RMB were associated with differences in service quality evaluation. Patients covered by urban and rural residents' medical insurance also showed variations in their evaluations. Conclusions The study highlights that smart healthcare services in public county-level hospitals fall short of meeting patients' expectations. It emphasizes the importance of addressing individualized medical needs and improving aspects such as cost control, system design, technology-human care balance, and operational efficiency.